Polychronicity and Intrinsic Motivation as Dispositional Determinants on Hotel Frontline Employees’ Job Satisfaction: Do Control Variables Make a Difference - Araslı, Hüseyin; Daşkın, Mustafa; Saydam, Serdar (Elsevier, 2014)
This empirical study aims to investigate the effect of polychronicity (POLY) and intrinsic motivation (INT) as dispositional antecedents on frontline employees’ (FLEs) job satisfaction (JSAT) in hotel setting in North Cyprus. PLS method was used to analyze the hypothesized relationships. This paper presented an integrative model to test the aforementioned effects and relationships. The findings depicted that there was a positive significant relationship between INT and JSAT. On the other hand, the relationship between POLY and JSAT was not significant Education as a control variable was found to be negatively related to FLEs’ job satisfaction. Also, tenure was found to be positively related with job satisfaction. In the hospitality management literature, there is a paucity of empirical research conducted to examine the impact of POLY and INT on JSAT. Therefore, the current study provides implications for managers and lends further contributions to the related literature as well.
The file in this item is the publisher version (published version) of the article.
Keywords: Frontline employees; Hotels; Polychronicity; Intrinsic motivation; North Cyprus; Job satisfaction